The Purpose of Forming a Communicative Interaction with Consumers ("Journal "U". Economy. Management. Finance.", 2023)
In a competitive environment, it is extremely difficult to attract consumers and keep their interest in any product or service. The methods that company use for promotion today may stop working tomorrow. Consumers are skeptical about many of the proposals of marketing specialists. In order for companies to successfully sell a product or service, it is necessary not only to monitor their quality, but also to accompany the sale with informative, original appeals that convince consumers that the goods meet their needs. In addition, the communication platform, when using appropriate methods, gives a competitive advantage to companies.
Keywords: communications; marketing; consumers; promotion